Plant Movement. Submergence-Induced Petiole Elongation in Rumex palustris Depends on Hyponastic Growth - Cox, Marjolein C.H. (American Society of Plant Biologists, 2003)
The submergence-tolerant species Rumex palustris (Sm.) responds to complete submergence by an increase in petiole angle with the horizontal. This hyponastic growth, in combination with stimulated elongation of the petiole, can bring the leaf tips above the water surface, thus restoring gas exchange and enabling survival. Using a computerized digital camera set-up the kinetics of this hyponastic petiole movement and stimulated petiole elongation were studied. The hyponastic growth is a relatively rapid process that starts after a lag phase of 1.5 to 3 h and is completed after 6 to 7 h. The kinetics of hyponastic growth depend on the initial angle of the petiole at the time of submergence, a factor showing considerable seasonal variation. For example, lower petiole angles at the time of submergence result in a shorter lag phase for hyponastic growth. This dependency of the hyponastic growth kinetics can be mimicked by experimentally manipulating the petiole angle at the time of submergence. Stimulated petiole elongation in response to complete submergence also shows kinetics that are dependent on the petiole angle at the time of submergence, with lower initial petiole angles resulting in a longer lag phase for petiole elongation. Angle manipulation experiments show that stimulated petiole elongation can only start when the petiole has reached an angle of 40° to 50°. The petiole can reach this “critical angle” for stimulated petiole elongation by the process of hyponastic growth. This research shows a functional dependency of one response to submergence in R. palustris (stimulated petiole elongation) on another response (hyponastic petiole growth), because petiole elongation can only contribute to the leaf reaching the water surface when the petiole has a more or less upright position.